2005
DOI: 10.1093/humrep/deh545
|View full text |Cite
|
Sign up to set email alerts
|

The morphological normalcy of the sperm nucleus and pregnancy rate of intracytoplasmic injection with morphologically selected sperm

Abstract: Implantation and pregnancy by ICSI is associated with morphological nuclear normalcy of sperm. Sperm with a morphologically abnormal nucleus usually have low fertility potential, but some with certain nuclear abnormalities may still be able to produce pregnancy following ICSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
186
0
15

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(206 citation statements)
references
References 16 publications
5
186
0
15
Order By: Relevance
“…Traditionally, semen parameters like sperm count, motility and morphology were considered for assessment of male factor. Of these, sperm morphology is much emphasized recently and is proven to be one of the important predictors in determining the fertilizing capacity of sperm both in vivo and in vitro conditions [23][24][25]. Several clinical studies have demonstrated a clear association between sperm head morphology and improvement in IVF success rate [4,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, semen parameters like sperm count, motility and morphology were considered for assessment of male factor. Of these, sperm morphology is much emphasized recently and is proven to be one of the important predictors in determining the fertilizing capacity of sperm both in vivo and in vitro conditions [23][24][25]. Several clinical studies have demonstrated a clear association between sperm head morphology and improvement in IVF success rate [4,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…All oocytes in both cycles showed one polar body and no pronuclei. In the three subsequent cycles, we applied IMSI [20] combined with AOA using fresh semen (Table 1). In the third cycle, 7/8 fresh MII donor oocytes were fertilized, and five developing embryos were obtained; two embryos were transferred at Day 3 (one with nine cells of unequal size, <10 % fragmentation; and one with six cells of unequal size, 0 % fragmentation); one non-compacted embryo was vitrified at Day 4 (eight cells of equal size, 0 % fragmentation).…”
Section: Semen Characteristics and Clinical Parameters Of Icsi Cyclesmentioning
confidence: 99%
“…49 The study design used by Bartoov's group was able to exclude the special sperm preparation technique needed for IMSI as the reason for higher implantation and pregnancy rates and lower miscarriage rates. 50 Performing diagnostic MSOME or therapeutic IMSI has several clinical limitations: (1) significant time and effort is needed for IMSI, because sperm selection can take several hours; (2) expertise and training is needed for these techniques; and (3) the cost of upgrading laboratory equipment to perform IMSI is significant. 50 Taking into account these issues, a diagnostic MSOME is advised in advance of IMSI to determine in which patients IMSI is likely to improve ICSI outcomes.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%